PSII-18 Effect of two different milk-feeding methods on performance and plasma glucose of dairy calves. (30th November 2020) - Silva, Marcos; Silva, Ana Paula; Toledo, Ariany; Dondé, Sophia; Tomaluski, Cristiane; Miranda, Fernanda Z; Brito, Gabriela; Bittar, Carla Maris M
Abstract: The objective of this study was to evaluate two different methods of milk feeding calves and the effects on performance and plasma glucose. Thirty newborn Holsteins calves were individually housed with free access to water and starter concentrate and fed 6 L/d of whole milk divided in two meals (7h and 17h). A randomized blocks experimental design was used, with weight and day of birth as blocking effect, and calves were distributed in two methods of milk-feeding: (1) open bucket; (2) bucket with an artificial teat. Milk-feeding period started with 3 d of age, after colostrum feeding by bottle. The starter intake was monitored daily. Speed of milk intake, body weight and measures, and blood samples were taken weekly. Data were analyzed using the proc mixed of SAS for repeated measures, and the means were compared using the F test (P ≤ 0.05). Feeding milk using a bucket with an artificial teat decreased average daily starter intake (P < 0.03), probably because calves were more satisfied by the act of suckling. However, there were no effects on body weight gain, weight at weaning and average body measures. The bucket with artificial teat had a positive influence on blood glucose concentration, measure 2h after milk feeding (P < 0.01), as a response of lower speed for milk intake (P < 0.01). These results suggest that the speed for milk intake may interfere on blood glucose concentrations peak, however because the behavioral need of suckling is attended, it may decrease starter intake, but without decrease performance.